Research methodology - Panneerselvam, R., author (PHI Learning Private Limited, 2014)
This comprehensive text designed for MBA, MCom, MA (Economics), MA (Sociology) and PhD (Management, Commerce, Economics, and Engineering) courses continues to give complete account of concepts and statistical tools of research methodology in its Second Edition. The textbook also serves as a reference for consultants to carryout [sic] projects/consultancies in industries or service organizations.
1. Overview of research methodology -- 2. Data collection and presentation -- 3. Review of basic statistical measures -- 4. Design and analysis of experiments -- 5. Attitude measurement and scales -- 6. Probability distributions -- 7. Sampling methods and distributions -- 8. Tests of Hypotheses -- 9. Nonparametric tests -- 10. Basic multivariate analysis -- 11. Advanced multivariate analysis -- 12. Multidimensional scaling and conjoint analysis -- 13. Algorithmic research -- 14. Models for industries and public systems -- 15. Simulation -- 16. Report writing and presentation -- 17. Introduction to SPSS -- Annexures -- Bibliography -- Answers -- Index.
Includes bibliographical references (pages 677-678) and index.
Keywords: Handbooks and manuals; Business Research Methodology; Social sciences Research Methodology; Sociology Research Methodology